Penentuan Potensi Wisata Prioritas melalui Pendekatan Community-Based Tourism di Desa Wisata Teritip Kota Balikpapan - Kiki Amalia Putri; Ajeng Nugrahaning Dewanti; Mohammad Muntaha (P4W LPPM IPB, 2017)
Desa Wisata Teritip (Teritip Tourism Village) is one of the new destinations of Balikpapan City which has 12 potential points for tourism, including the potential of site attraction (nature’s beauty) and the potential of event attraction (community culture and tourism activities). However, these potentials has not been utilized and developed optimally by the local community up to now. The development is constrained by the lack of community involvement in managing the tourism village. The purpose of this study was to identify priority tourism potentials to be developed through community-based approaches in order to put the role of the local community as subject and object of the development of the village. This study uses rationalistic approach with a qualitative descriptive method. The analysis technique used to answer the research objectives, are: on the first stage, content analysis was used to analyze the potential tourism attractions to be developed; and followed by the second stage, a descriptive qualitative analysis to identify potential tourism attraction priorities for development by emphasizing the role of local communities.The result obtained is that the three factors of attractiveness: nature’s beauty, community culture and tourism activities, has the potential to be develop through community-based approaches and there are 10 potential tourism priorities to be developed, which covers physical, socio-cultural, and supporting tourism objects.